How the Student’s Error in Solution of Mathematics Problems? - Novianti, Dwi Erna (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2019)
This qualitative descriptive study aimed to analyze student errors to solve mathematical problems in gender. The subject in this research were Mathematics Education students in the Linear Program subject. The sample selection used purposive sampling by looking at the results of student tests on linear program material categorized by gender. The analysis data using observation methods, test methods and interview methods, meanwhile to validity test of the data using triangulation of data source and triangulation method. Based on the results of the study obtained results: 1) Errors experienced by male and female students are almost similar, but the mistakes experienced by female students are fewer than male students, 2) Female and male students with high ability categories possess different types of errors, namely female students only experience process errors and results of errors, while male experience transformation errors, process errors, results in errors, 3) Female and male students with low ability categories have the same type of errors, namely misunderstanding, transformation errors, process errors, results errors. In this study also none of the subjects experienced reading errors.